Active Choice Format and Minimum Payment Warnings in Credit Card Repayment Decisions. Issue 3 (July 2020) - Salisbury, Linda Court; Zhao, Min
The increasingly common online credit card repayment formats typically involve consumers' active choice from among various payment amounts. Consumers rarely view minimum payment warning (MPW) disclosures while repaying online; therefore, the common shift toward online repayment means that the MPW is not salient for most credit cardholders. This article aims to shed light on credit cardholders' payment decisions under this "active choice format" and explore effective online interfaces for payment decisions. Drawing on research in active choice, the authors demonstrate in three experiments that, compared with the "open format" used in traditional monthly statements, active choice format increases consumers' full balance payment propensity and overall repayment amount, and this effect is even stronger when current account balance is included in the choice context. Furthermore, presence of the MPW disclosure significantly decreases payment of the minimum required amount and increases payment of the "three-year payoff amount." Finally, presence of MPW increased consumer feelings about making the right decision, primarily for financially vulnerable people. These findings, based on hypothetical scenario choices, offer interesting theoretical and important policy implications.